THE EFFECT OF OPHIOCEPHALUS STRIATUS EXTRACTS ON TUMOR NECROSIS FACTOR-α (TNF-α) SERUM IN CANCER CACHEXIA PATIENTS - Apriani, Dairion Gatot & Senior Tawarta (International Journal of Research Science and Management, 2019)
Introduction: One of the most common manifestations of advanced cancer is the development of metabolic symptoms called cancer cachexia. TNF-α hyperexpression has been identified as one of the key cytokine responses involved in cachexia, that continuously results in progressive anorexia and weight loss. In addition, TNF-α appears to affect several cachexia cancer abnormalities: decreased adipose and muscle wasting, and changes in fat and protein metabolism. Ophiocephalus striatus extract can be considered as a potential natural support to have anti-inflammatory properties, decrease regulation of both pro-inflammatory cytokine production and acute phase protein responses in cancer patients. Aim: The objective of this study is to find the effect of Ophiocephalus striatus extract supplementation and TNF-α plasma level in patient with cancer cachexia. Method: This study was an open label study in which all subject knew the purpose of this study and understood the intervention they will get. The design for this study was one group pretest and posttest with inclusion and exclusion criteria to choose the ideal subject for this study. Descriptive statistics analysis used for demographic data and Wilcoxon test used to test numeric variable in study treatment groups before and after treatment and p <0.05 was considered significant. Subjects were treated with supplementation which contains 5000 mg Ophiocephalus striatus extract in twice daily 2 weeks period. Result: The result from this study shows decreased in TNF-α plasma level before (7,83 pg/mL) and after treatment (3,82 pg/mL) with Ophiocephalus striatus extract (p=0.004). And this study also showed an increase in albumin plasma levels before and after treatment with Ophiocephalus striatus extract (p < 0.001). Conclusion: The effect of Ophiocephalus striatus extract decreased in TNF-α plasma level and an increase in albumin plasma levels before and after treatment, and statistically significant.